Estimating normal duration of renovation for multistory apartment building considering extension-type renovation projects - Yoon, Jongsik; Yu, Ilhan (Journal of Civil Engineering and Management, 2019)
Normal (typical) project duration is estimated at the initial stage of a renovation project and is an important reference for project control. However, its estimation has not been researched extensively owing to the complexity and uncertainties of renovation. Thus, a model was developed for predicting the duration of sustainable apartment renovation. Experts were asked to estimate a baseline schedule for extension-type renovation projects, factors that influence critical path activities, and the range of project durations considering these factors. An equation for estimating the duration of a renovation project was developed, and the range of project durations was derived using a MCS to reflect uncertainty. The proposed model was validated by applying it to actual cases. The case study shows that the model would be more suitable for complex renovation construction (i.e., more than two buildings or vertical extension). The model can be applied to various renovation projects and used as a reference for determining contract time. It can fill the knowledge gap of construction duration forecasting by adapting the concept of control activities to simplify the assessment of uncertainties in renovation of apartments, and can be applied for forecasting sustainable renovation time for other project types or in other locations.